Nominal Gender in Coptic Egyptian: Typology and Morphological Analysis - Bendjaballah, Sabrina (Zeitschrift für ägyptische Sprache und Altertumskunde, 2021)
The interdisciplinary research (philology, typology, morphology, phonology) presented here explores the role of gender in the meaning and morphology of Coptic nouns. Coptic has a predominantly grammatical gender system, albeit with a niche for semantically based gender assignment. The gender system marks a three-way semantic contrast between a [male] versus a [female] versus an [unspecified] gender value, even where the morphology draws only a two-way distinction between grammatical masculine and feminine gender. By integrating quantitative data and morphophonological analysis, we shall argue that masculine gender is morphologically unmarked. Although no discrete morpheme can be identified, feminine gender is always morphologically marked on nouns. Masculine and feminine nouns are distinguished in terms of their templatic structure, which interacts in complex ways with vowel distributions, stress assignment, and noun class.